Senyawa bioaktif dan potensi bekatul beras (Oryza sativa) sebagai bahan pangan fungsional - Teti Estiasih; Kgs Ahmadi; Vania Santoso (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Rice bran is one of the by-products of rice milling with an amount produced about 8% of the weight of rice. The high rice production in Indonesia resulted in a high amount of bran produced with an estimated 2.15 million tons. The rice bran availability is very high, but it has not been optimally utilized for the food industry as an ingredient. Besides white rice, red and black rice is currently being consumed in Indonesia. Bran produced from different rice varieties has different compositions and characteristics. The characteristics of red and black rice bran are still not much explored. In addition to containing macro components such as protein, oil, starch, and fiber, rice bran also contains bioactive compounds i.e., phenols, flavonoids, phytosterols, gamma oryzanol, tocotrienols, and tocopherols, squalene, and polycosanols. The macro components in bran are precious ingredients for the food industry to develop functional foods. The limiting factor in the formulation of rice bran in food products is the change in palatability and product characteristics. This functional food containing rice bran is a superfood that contains multicomponent bioactive compounds that can work synergistically to modulate positive effects on health.